Sistem Penjaminan Mutu Pendidikan di MTs Riyadush Sholihin Purwareja Klampok Banjarnegara - Sudiro Sudiro; Alya Az Zahra; Muhammad Ali Jazuli; Ahmad Bagus Romadhon; Dian Islamiati (Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Abstract The quality of education is related to whether or not the goals of national education are achieved as stated in Law No. 20 of 2003 concerning the National Education System. Therefore, the quality of education can be said to be good if it meets the National Education Standards. Fulfillment of the minimum standard of education which is the National Education Standard is a requirement to improve the quality of education including madrasah. The reality that emerges is that the quality of education in Indonesia is still quite far from what was expected, moreover the quality in most madrasas is still experiencing many problems. Many madrasahs do not meet standardized qualifications and competencies, as well as inadequate facilities and infrastructure. This paper aims to describe the role of the education quality assurance system in improving the quality of education in madrasas. Keywords: Quality, Education, Madrasah, National Standards. Abstrak Mutu pendidikan berkaitan dengan tercapai atau tidaknya tujuan pendidikan nasional seperti yang tercantum di dalam UU Nom 20 Tahun 2003 tentang Sistem Pendidikan Nasional. Oleh karena itu, mutu pendidikan dapat dikatakan baik apabila memenuhi Standar Nasional Pendidikan. Terpenuhinya standar minimal pendidikan yang merupakan Standar Nasional Pendidikan merupakan persyarat untuk meningkatkan mutu pendidikan termasuk madrasah. Realitas yang muncul bahwa mutu pendidikan di Indonesia masih cukup jauh dari yang diharapkan, apalagi mutu di kebanyakan madrasah yang masih banyak mengalami kendala. Banyak madrasah yang belum memenuhi kualifikasi dan kompetensi yang distandarkan, serta sarana dan prasarana yang belum memadai. Tulisan ini bertujuan untuk mendeskripsikan bagaimana peran sistem penjaminan mutu pendidikan dalam meningkatkan mutu pendidikan di madrasah. Kata Kunci : Mutu, Pendidikan, Madrasah, Standar Nasional.